Simulation and analysis of different heating method for bio-digester substrate. (2022) - Kamala, Shiksha; Arun Chandran, P.; Hareesh Krishnan, H.; Glivin, Godwin; Sudhakar, Ruben; Premalatha, M.; Mariappan, V.; Sekhar, Joseph
Abstract: This report is on topic of simulation and analysis of different heating method for bio-digester substrate. Now-a-days the energy demand is increasing so we have to look other options and devise a method to optimize the production from other sources. Due to Covid-19 mass migration and increased hospital admission occurs, to fulfill the food supply biogas is sought. This report focus on digesters on a small scale that can be employed for household activities. To increase the biogas yield among different influencing factors temperature is chosen and worked upon. Along with insulation there is a heating method installed to maintain the stable temperature which facilitates breakdown of organic materials and improve the productivity. In colder climates maintaining mesophilic temperature can be a challenge, therefore three heating methods are simulated and analyzed. The study reveals about floor heating, in-vessel heating and floor + in-vessel heating method. In-vessel heating method provides uniform cooling, whereas floor heating can be applied at relatively cold climates because it give significant temperature rise (about ∼14 °C). Out of these three methods floor + in-vessel heating method is found suitable as it optimize the benefits of both floor and in-vessel heating methods with 5 °C temperature raise.